The RFC2 Gene, Encoding the Third-Largest Subunit of the Replication Factor C Complex, Is Required for an S-Phase Checkpoint in Saccharomyces cerevisiae - Noskov, Vladimir N. (American Society for Microbiology, 1998)
Replication factor C (RF-C), an auxiliary factor for DNA polymerases δ and ɛ, is a multiprotein complex consisting of five different polypeptides. It recognizes a primer on a template DNA, binds to a primer terminus, and helps load proliferating cell nuclear antigen onto the DNA template. The RFC2 gene encodes the third-largest subunit of the RF-C complex. To elucidate the role of this subunit in DNA metabolism, we isolated a thermosensitive mutation (rfc2-1) in the RFC2 gene. It was shown that mutant cells having the rfc2-1 mutation exhibit (i) temperature-sensitive cell growth; (ii) defects in the integrity of chromosomal DNA at restrictive temperatures; (iii) progression through cell cycle without definitive terminal morphology and rapid loss of cell viability at restrictive temperatures; (iv) sensitivity to hydroxyurea, methyl methanesulfonate, and UV light; and (v) increased rate of spontaneous mitotic recombination and chromosome loss. These phenotypes of the mutant suggest that the RFC2 gene product is required not only for chromosomal DNA replication but also for a cell cycle checkpoint. It was also shown that the rfc2-1 mutation is synthetically lethal with either the cdc44-1 or rfc5-1 mutation and that the restrictive temperature of rfc2-1 mutant cells can be lowered by combining either with the cdc2-2 or pol2-11 mutation. Finally, it was shown that the temperature-sensitive cell growth phenotype and checkpoint defect of the rfc2-1 mutation can be suppressed by a multicopy plasmid containing the RFC5 gene. These results suggest that the RFC2 gene product interacts with the CDC44/RFC1 and RFC5 gene products in the RF-C complex and with both DNA polymerases δ and ɛ during chromosomal DNA replication.